Effects of the pandemic on women's reproductive health protective attitudes: a Turkish sample - Derya Kaya Senol; Filiz Polat (BMC, 2022)
Plain language summary Impairment of sexual and reproductive health (SRH) and inability to use sexual and reproductive rights are an important public health problem during pandemics. Reproductive healthcare services are limited to pregnancy and childbirth-related care during pandemics. This study was conducted to examine the effects of the pandemic on women's protective attitudes towards reproductive health. In women in Turkey, education level, income status, health assurance, health perceptions, obstetric history and contraceptive methods are the factors that affect the reproductive health. The women presenting to health centers with reproductive health problems before a pandemic do not receive healthcare for their genital problems during the pandemic due to the risk of disease transmission.